Development of research skills from the experience of Engineering students - Tacca Huamán, Daniel Rubén (Journal of the University of Zulia, 2021)
Research is an important aspect in the professional training of young university students, so the main objective of the present work was to know how research skills have been developed from the experience of Engineering students. The work was developed under a qualitative approach, with a phenomenological design, and interviews were conducted with 18 students who were in the last year of professional engineering studies at a private university in Lima, Peru. The results indicate that students are able to conceptualize and recognize some investigative skills, giving little relevance to methodological and communication skills. For those interviewed, the university promotes research in the last years of study, but it would be recommended that they be transversal to all subjects. Additionally, as explained by the participants, it is necessary for teachers to be researchers and not research theorists.